Graduates' perceptions of their midwifery training during the four year comprehensive nursing diploma - R Chetty; NS Gwele (AOSIS, 2001)
Since its inception in 1986, the Comprehensive Nursing Diploma has received many criticisms from registered nurses, who graduated from the pre-existing programmes. This study attempts to examine the perceptions of graduates from this training programme, towards their midwifery education in terms of its adequacy in preparing them for midwifery practice. Twenty-nine graduates of the four year Comprehensive Nursing Programme completed self-administered questionnaires. Data was analysed by means of descriptive and inferential statistics, namely the paired t-test and the Wilcoxon test for matched pairs. Qualitative data was analysed to determine emerging themes and patterns. Differences in competence ratings on entry into midwifery units and those a year later, were significant at p = 0.0001. It was found that graduates appear to have a positive perception of the midwifery component of their training programme. They found the theory aspect to be more than adequate in preparing them for their professional roles. However, with regards to clinical exposure, it was felt that the time period was too short and needed to be extended in order for them to attain clinical proficiency.